Analisis Pengaruh Pola Asuh Orang Tua Terhadap Perilaku Belajar Siswa SMPN 14 Kota Serang - Sela Marselina; Silvia Agustina; Salwa Sabrina; Pebri Apriyansyah; Adriansyah Adriansyah; M. Ayi Nuriani; Eko Ribawati (Universitas Palangka Raya, 2025)
This study aims to determine the effect of parenting on the learning behavior of students SMPN 14 Kota Serang. This type of research is qualitative. The sample in this study were students SMPN 14 Kota Serang and their parents who raised them. The data collection method used is a questionnaire. The data analysis technique used is descriptive analysis. The results of the research data on the learning response indicators show that the respondents have a fairly good response in learning, as evidenced by a score of 270. The learning enthusiasm indicator shows that the respondents have very good learning enthusiasm, as evidenced by a score of 348. The responsible indicator shows that the respondent has a very good sense of responsibility, as evidenced by a score of 348. The technical indicator in learning shows that the respondent has excellent learning techniques, as evidenced by a score of 405. The study habit indicator shows that the respondent has a fairly good study habit, as evidenced by a score of 307. The observation and thinking indicator when studying shows that the respondent has fairly good observation and thinking when studying, as evidenced by a score of 283. On the indicator of continuous interaction of parents and children, it shows that the interaction of parents and respondents continuously is quite good, as evidenced by a score of 456. On the indicator of a series of decisions on socialization shows that respondents have a series of decisions that are quite good about socialization, as evidenced by a score of 487 The indicator of the influence of social institutions shows that the respondent has a fairly good influence of social institutions, as evidenced by a score of 283. The indicator of the influence of culture shows that the respondent has a very good cultural influence, as evidenced by a score of 376. parents have quite an effect on student learning behavior. It is proven by the responses of students SMPN 14 Kota Serang with a score of 3563.